The Dimension of Student Engagement in Qur'anic Literacy Learning: A Case Study of Kokoda Tribe Students at MTs Emeyodere - Fikri Hakim Putra; Agus Yudiawan; Fatma Sari (al-Afkar, Journal For Islamic Studies, 2026)
Qur'anic literacy among minority communities, such as the Kokoda Tribe, faces significant challenges, particularly in Qur'anic reading and writing learning (BTQ). This study aims to analyze the engagement of Kokoda Tribe students in BTQ learning, focusing on three aspects: behavioral, emotional, and cognitive. Using a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews with students and teachers, and documentation of learning activities at MTs Emeyodere. The findings show that student engagement is greatly influenced by emotional factors, especially curiosity about the Qur'an. Students demonstrate high behavioral engagement in physical activities during lessons, although cognitive challenges, such as Arabic letter pronunciation influenced by local dialects, remain obstacles. This study concludes that social and cultural factors strongly affect student engagement in Qur'anic learning, with emotional engagement more dominant than cognitive. The implication of this research is the importance of teaching approaches that consider students' cultural backgrounds to improve the effectiveness of Qur'anic learning.